(a2+b2)(a4-a2b2+b4)-(a3-b3)(a3+b3)=2b6

0 голосов
270 просмотров

(a2+b2)(a4-a2b2+b4)-(a3-b3)(a3+b3)=2b6


Алгебра (72 баллов) | 270 просмотров
0

Ugh

0

Довести тотожность

0

im not Russian

0

а это украинский...

0

nope,do u love kebab ?

Дано ответов: 2
0 голосов
Правильный ответ

Решите задачу:

\underbrace {(a^2+b^2)(a^4-a^2b^2+b^4)}_{(a^2)^3+(b^2)^3}-\underbrace {(a^3-b^3)(a^3+b^3)}_{(a^3)^2-(b^3)^2}=\\\\=(a^2)^3+(b^2)^3-\Big ((a^3)^2-(b^3)^2\Big )=a^6+b^6-a^6+b^6=2b^6\\\\\\\star \; \; (x+y)^3=(x+y)(x^2-xy+y^2)\; \; \star \\\\\star \; \; (x-y)(x+y)=x^2-y^2\; \; \star

(835k баллов)
0 голосов

(a²+b²)(a⁴-a²b²+b⁴)-(a³-b³)(a³+b³)=

(a²)³+(b²)³-(a³)²+(b³)²=

a^6+b^6-a^6+b^6=2b^6

(30.0k баллов)